"If you don't behave, you're in real shit, you don't get outside the doors"—a phenomenological hermeneutic study of adolescents' lived experiences of the socio-spatial environment of involuntary institutional care. Issue 1 (1st January 2020) - Nolbeck, Kajsa; Wijk, Helle; Lindahl, Göran; Olausson, Sepideh
ABSTRACT: In Sweden, according to law, adolescents with extensive psychosocial problems, substance abuse or criminal behaviour can be cared for in institutions. The two-fold aim of these institutions (to rehabilitate and incarcerate) puts special demands to their socio-spatial context. Purpose : To elucidate adolescents' lived experiences of the socio-spatial environment at special youth homes run by the Swedish National Board of Institutional Care (SiS) in Sweden. Methods : Data collected through Photovoice and analysed employing a phenomenological hermeneutical method. Fourteen adolescents (age 15–19) were asked to photograph their environment, and this was followed up by in-depth interviews. Results : Two themes emerged from the material: the dense walls of institutional life and create and capture the caring space . The socio-spatial environment can be seen as an additional "other" that distances the adolescents and the staff from one another. Negotiating with their behaviour, the adolescents strive to present themselves as worthy of increased degrees of freedom and ultimately access to the desired outside life. Conclusions : In an institutional setting dominated by a security and criminal justice logic, words appear to have less impact than the environment. The adolescents appear to understand themselves through the socio-spatial other, causing reinforced feelings of social exclusion.